Cloning of the URA1 gene of Saccharomyces cerevisiae. - Guerry-Kopecko, P (1980)
A 5.7-kilobase segment of Saccharomyces cerevisiae deoxyribonucleic acid which complements both the yeast ura1 and Escherichia coli pyrD mutations in dihydroorotate dehydrogenase has been cloned in plasmid YRp7.